A retrotransposon-derived DNA zip code internalizes myeloma cells through Clathrin-Rab5a-mediated endocytosis - Puvvula, Pavan Kumar; Martinez-Medina, Lourdes; Cinar, Munevver; Feng, Lei; Pisarev, Andrey; Johnson, Anthony; Bernal-Mizrachi, Leon (Frontiers in Oncology, 2024)
The present research aimed to investigate the cellular uptake and intracellular trafficking of MM-ZC, a cell-specific Zip-Code, in myeloma cell lines. We demonstrated that MM-ZC uptake by myeloma cells was concentration-, time-and cell-type-dependent. By utilizing the various endocytosis inhibitors, we found that Monensin and Chlorpromazine hydrochloride significantly reduced MM-ZC internalization. These findings suggested that Clathrin-mediated endocytosis and endosomal maturation play a crucial role in the cellular uptake of MM-ZC. In addition, biotin pulldown and confocal microscopic studies revealed the involvement of proteins such as Clathrin, Rab5a, Syntaxin-6, and RCAS1 in facilitating the internalization of MM-ZC. Knockdown of Rab5a and Clathrin proteins reduced cellular uptake of MM-ZC and conclusively demonstrated the involvement of Clathrin-Rab5a pathways in MM-ZC endocytosis. Furthermore, both Rab5a and Clathrin reciprocally affected their association with MM-ZC when we depleted their proteins by siRNAs. Additionally, the loss of Rab5a decreased the Syntaxin-6 association with MM-ZC but not vice versa. Conversely, MM-ZC treatment enhanced the association between Clathrin and Rab5a. Overall, the current study provides valuable insights into the cellular uptake and intracellular trafficking of MM-ZC in myeloma cells. Identifying these mechanisms and molecular players involved in MM-ZC uptake contributes to a better understanding of the delivery and potential applications of cell-specific Zip-Codes in gene delivery and drug targeting in cancer research.